Is elevation encoded in cognitive maps? - Garling, Tommy; Böök, Anders; Lindberg, Erik; Arce, Constantino (Journal of environmental psychology, 1990)
Two experiments examined whether differences in elevation of the terrain are encoded in cognitive maps of outdoor environments. In Experiment 1, two groups of subjects who had travelled a varying number of times between a set of locations made direct estimates in metres of the differences in elevation between the locations. The results showed that subjects in both groups had knowledge of elevation but those for whom the terrain was less familiar tended to exaggerate the differences. In Experiment 2, decision times were measured of responses to the question whether one location is below or above another one. Neither for subjects who were more, nor for subjects who were less familiar with the terrain, did the decision times vary with the distances between the locations, thus failing to support the hypothesis that differences in elevation are retrieved by a process of ‘mental travel’.